2010
DOI: 10.1039/b918209h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation and coupling of aqueous phenolics over bifunctional zeolite-supported metal catalysts

Abstract: Pt supported on HY zeolite is successfully used as a bifunctional catalyst for phenol hydrodeoxygenation in a fixed-bed configuration at elevated hydrogen pressures, leading to hydrogenation-hydrogenolysis ring-coupling reactions producing hydrocarbons, some with enhanced molecular weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
207
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(218 citation statements)
references
References 29 publications
(38 reference statements)
9
207
0
2
Order By: Relevance
“…Meanwhile, alkylation and etherification take place to form bicyclic compounds. Hong et al also reported similar reaction pathways of phenol to bicyclics over Pt/HY catalyst [27]. Studies on both aqueous-phase and vapor-phase HDO of phenol indicated that non-sulfide catalysts favor HYD route to saturate the aromatic ring.…”
Section: Propertymentioning
confidence: 71%
“…Meanwhile, alkylation and etherification take place to form bicyclic compounds. Hong et al also reported similar reaction pathways of phenol to bicyclics over Pt/HY catalyst [27]. Studies on both aqueous-phase and vapor-phase HDO of phenol indicated that non-sulfide catalysts favor HYD route to saturate the aromatic ring.…”
Section: Propertymentioning
confidence: 71%
“…have differing rates, and different catalysts will promote DDO or HYD as a primary reaction depending on the nature of the metal and the support [10]. It has been observed that noble metals favor HYD whereas sulfided catalysts preferentially undergo DDO reactions [23], [24]. In addition to facilitating multiple reactions, an ideal bifunctional catalyst should still be able to exhibit a high turnover frequency (TOF) and the capability to maintain this activity after repeated trials.…”
Section: Bifunctional Catalysismentioning
confidence: 99%
“…Hydroalkylation involves ring-coupling of phenol with cyclohexanol or cyclohexene on Brønsted acidic materials, resulting in the formation of bi-cyclic or tri-cyclic oxygenates, that can then undergo subsequent hydrodeoxygenation [30][31][32]. While most of the work on hydroalkylation of biomassderived phenolics has been performed in the aqueous liquid phase [30,32], ring coupling has been observed in the vapor phase at temperatures similar to the operating temperature of fixed bed reactor #2 [33]. Accordingly, hydroalkylation will be targeted in reactor #2.…”
Section: Reaction Chemistry and Catalyst Optionsmentioning
confidence: 99%
“…This approach combining upstream ketonization with downstream aldol condensation and hydrogenation-dehydration provides a promising route for converting carboxylic acids into diesel/jet fuel range products [22,[26][27][28]. Hydroalkylation involves ring-coupling of phenol with cyclohexanol or cyclohexene on Brønsted acidic materials, resulting in the formation of bi-cyclic or tri-cyclic oxygenates, that can then undergo subsequent hydrodeoxygenation [30][31][32]. While most of the work on hydroalkylation of biomassderived phenolics has been performed in the aqueous liquid phase [30,32], ring coupling has been observed in the vapor phase at temperatures similar to the operating temperature of fixed bed reactor #2 [33].…”
Section: Reaction Chemistry and Catalyst Optionsmentioning
confidence: 99%